Efficient Differentiation of Human Induced Pluripotent Stem Cells into Endothelial Cells under Xenogeneic-free Conditions for Vascular Tissue Engineering. (1st January 2021) - Luo, Jiesi; Shi, Xiangyu; Lin, Yuyao; Yuan, Yifan; Kural, Mehmet H.; Wang, Juan; Ellis, Matthew W.; Anderson, Christopher W.; Zhang, Shang-Min; Riaz, Muhammad; Niklason, Laura E.; Qyang, Yibing
Abstract: Tissue engineered vascular grafts (TEVGs) represent a promising therapeutic option for emergency vascular intervention. Although the application of small-diameter TEVGs using patient-specific primary endothelial cells (ECs) to prevent thrombosis and occlusion prior to implantation could be hindered by the long time course required for in vitro endothelialization, human induced pluripotent stem cells (hiPSCs) provide a robust source to derive immunocompatible ECs (hiPSC-ECs) for immediate TEVG endothelialization. To achieve clinical application, hiPSC-ECs should be derived under culture conditions without the use of animal-derived reagents (xenogeneic-free conditions), to avoid unwanted host immune responses from xenogeneic reagents. However, a completely xenogeneic-free method of hiPSC-EC generation has not previously been established. Herein, we substituted animal-derived reagents used in a standard method of xenogeneic hiPSC-EC differentiation with functional counterparts of human origin. As a result, we generated xenogeneic-free hiPSC-ECs (XF-hiPSC-ECs) with similar marker expression and function to those of human primary ECs. Furthermore, XF-hiPSC-ECs functionally responded to shear stress with typical cell alignment and gene expression. Finally, we successfully endothelialized decellularized human vessels with XF-hiPSC-ECs in a dynamic bioreactor system. In conclusion, we developed xenogeneic-free conditions for generating functional hiPSC-ECs suitable for vascular tissue engineering, which will further move TEVG therapy toward clinical application. Graphical abstract: Image, graphical abstract